Clopidogrel, ticagrelor, prasugrel or an alternation of two P2Y12 in patients with acute myocardial infarction with cardiogenic shock - Kanic, Vojko; Kompara, Gregor (Frontiers in Cardiovascular Medicine, 2024)
Data are lacking on the effects of the alternation of P2Y12 receptor antagonists (P2Y12) on bleeding and outcome in patients with myocardial infarction (MI) with cardiogenic shock (CS). We compared the effects of different P2Y12 and alternation of P2Y12 (combination) on bleeding and outcome in patients with MI and CS.Data from 247 patients divided into four groups: clopidogrel, ticagrelor, prasugrel, and the combination group, were analyzed. The association between P2Y12 and bleeding as well as 30-day and one-year mortality was examined.The highest bleeding rate was observed in patients in the combination group, followed by the clopidogrel, ticagrelor, and prasugrel groups [12(50%) patients, 22(28.2%), 21(18.3%) and 4(13.3%), respectively;p=0.003]. Bleeding occurred with a similar frequency in the combination and clopidogrel groups (p=0.081), but more frequently than in the ticagrelor and prasugrel groups(p=0.002 and p=0.006, respectively). Bleeding rates were similar in patients receiving P2Y12 alone (p=0.13). Compared to clopidogrel, both ticagrelor and prasugrel had a lower bleeding risk (aOR 0.40;95%CI 0.18-0.92;p=0.032 and aOR 0.20;95%CI 0.05-0.85;p=0.029, respectively) and the combination had a similar bleeding risk (aOR 2.31;95%CI 0.71-7.48;p=0.16). The ticagrelor and prasugrel groups had more than an 80% and 90% lower bleeding risk than the combination group (aOR 0.17;95%CI 0.06-0.55;p=0.003 and aOR 0.09;95%CI 0.02-0.44;p=0.003, respectively). The unadjusted 30-day and one-year mortality were highest in the clopidogrel group, followed by the ticagrelor, prasugrel, and combination groups (44(56.4%) and 55(70.5%) patients died in the clopidogrel group, 53(46.1%) and 56(48.7%) in the ticagrelor group, 12(40%) and 14(46.7%) patients died in the prasugrel, and 6(25%) and 9(37.5%) patients died in the combination group within 30 days and after one year; p=0.045 and p<0.0001. After adjustment for confounders, the P2Y12 groups were not independently associated with either 30-day (p=0.23) or one-year (p=0.17) mortality risk.Our results suggest that the choice of P2Y12 was not associated with treatment outcome. The combination of P2Y12 increased bleeding risk compared with ticagrelor and prasugrel and was comparable to clopidogrel in patients with MI and CS. However, these higher bleeding rates did not result in worse treatment outcomes.